Acute neuromuscular and fatigue responses to the rest-pause method - Marshall, P. W. M.; Robbins, D. A.; Wrightson, A. W.; Siegler, J. C. (Journal of Science and Medicine in Sport, 2012)
Objectives To compare muscle recruitment, maximal force, and rate of force development changes following different resistance exercise protocols with a constant volume-load. Design